PENGARUH DISIPLIN KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PT SRIBOGA MARUGAME UDON CABANG MALL TAMAN ANGGREK DAN CABANG MALL NEO SOHO DAERAH JAKARTA BARAT - Damayanti, Arindi; Nelsi, Mitri (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of work discipline and career development on employee performance either partially or simultaneously. The method used in this research is a associative method with a quantitative approach, the research population is 56 people and all of the population is used as respondents. Data collection was carried out by distributing questionnaires to employees of PT. Sriboga Marugame Udon Branch West Jakarta. Data analysis using validity test, reliability test, classical assumption test, regression analysis and hypothesis testing. The research results show that work discipline has a positive and significant effect on employee performance with the regression equation value Y= 9.506 + 0.880 (X1) hypothesis test obtained value Tcount > Ttable (8,082 >1,673) H1 is accepted meaning that there is a psitive and significant influence difference between work discipline and employee performance. Career Development has a positive and significant effect on employee performance with the regression equation value Y = 11,718 + 0996 (X2) hypothesis test obtained value Tcount > Ttable (12,083 > 1,673) H2 is accepted meaning that there is a psitive and significant influence difference between Career Development on employee performance. Work Discipline and Career Development have a positive and significant effect on employee performance with the regression equation value Y = 1.232 + 0.990 (X1) + 0.998 (X2) hypothesis test obtained value Fcount > Ftablel (79.467 > 3,16) H3 is accepted, meaning that there is a positive and significant influence between work discipline and career development on employee performance at PT. Sriboga Marugame Udon Branch West Jakarta.